Chemopreventive effects of Xiang Sha Liu Jun Zi Tang on paclitaxel-induced leucopenia and neuropathy in animals - Shiah, Her-Shyong; Lee, Chia-Jung; Lee, Fang-Yu; Tseng, Sung-Hui; Chen, Shih-Han; Wang, Ching-Chiung (Frontiers in Pharmacology, 2023)
Paclitaxel frequently induces peripheral neuropathy and myelosuppression during cancer treatment. According to the National Health Insurance Research Database of Taiwan, traditional Chinese medicine doctors widely use Xiang Sha Liu Jun Zi Tang (XSLJZT) to treat breast cancer patients who have received paclitaxel. We explored the combined therapeutic effects of XSLZJT with paclitaxel. XSLJZT did not exhibit significant cytotoxic effects on P388-D1 cells; however, the combination of XSLJZT (100 and 500 mg/kg) with paclitaxel prolonged the survival rate in P388–D1 tumor-bearing mice compared to paclitaxel-only. In addition, XSLJZT was found to enhance WBC counts and promote leukocyte rebound in paclitaxel-induced leukopenia in mice. XSLJZT also reduced paclitaxel-induced mechanical pain and inhibited c-Fos protein expression in the L4-6 spinal cords of Wistar rats. Moreover, paclitaxel-induced shortening of the nerve fibers of dorsal root ganglion cells was ameliorated by pre-treatment with XSLJZT. Therefore, we suggest that XSLJZT could be used as an adjunct for cancer patients, as the formula could decrease paclitaxel-induced neuropathy and myelosuppression.